Applying an animal‐centric approach to improve ecological restoration. Issue 6 (20th October 2016) - Jones, Menna E.; Davidson, Neil
Abstract: Traditionally, ecological restoration is based on re‐establishing patterns of vegetation communities with the expectation that wildlife will recolonize, restoring the ecological function. However, in many restoration projects, wildlife fails to recolonize, even when vegetation is restored, in many cases because revegetated habitats lack the critical features required by wildlife. We present a new approach to restoration, based on a detailed understanding of ecological process, the mechanisms by which wildlife respond to landscape patterns. Our animal‐centric approach involves measuring the risk‐sensitive decision‐making of individual animals as they balance searching for food, mates, and breeding sites with avoiding being eaten by predators and relates this to fine‐scale habitat and landscape structure. The outcome of these decisions can be measured in occupancy of habitat, the information on which conventional restoration is based. Incorporating landscape genetics allows retrospective assessment of the outcome of dispersal decisions by individual animals on a deeper time frame and at regional scales. Fine‐scale connectivity models can be parameterized with these multiscale spatial and temporal data to direct restoration efforts. We are translating this novel approach to practice in the large Midlands restoration project (4 years, AUD $6 million) in Tasmania, Australia, in partnership with Greening Australia. More than 200 years of intensive agricultural practice in this National Biodiversity Hotspot has resulted in extensive landscape modification, high densities of feral cats, and decline of many native mammals. Our research–practice partnership will alter the way that restoration is done, leading hopefully to successful restoration of wildlife, gene flow, and ecological function.